ANALISIS PENGARUH INFLASI DAN SUKU BUNGA SERTIFIKAT BANK INDONESIA TERHADAP NILAI OBLIGASI SYARIAH DARI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - B2091141025, KRISTINA SANJAYA (MAKSI, 2017)
This study aimed to analyze the influence of Inflation and Interest Rates against Sharia Bond Index of Companies Listed in Indonesia Stock Exchange. This study focuses on the study of the field of capital market accounting year observation period 2011 - 2016 to enterprises that trade Islamic bonds in the Indonesia Stock Exchange. This study uses multiple linear regression in the form of studies that tested the hypothesis to explain the effect of inflation and SBI among variables against Islamic bond index. The results showed that inflation is not significant effect on the index while the Islamic bond SBI rate significantly influence the Islamic bond index.Keywords: Inflation, Interest Rates, Index Islamic Bonds